解方程:(1+x)[2(-36x)^2/(9x+1)^2-4(72x-9)/(9x+1)]=4........
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/08 02:07:26
解方程:(1+x)[2(-36x)^2/(9x+1)^2-4(72x-9)/(9x+1)]=4........解方程:(1+x)[2(-36x)^2/(9x+1)^2-4(72x-9)/(9x+1)]
解方程:(1+x)[2(-36x)^2/(9x+1)^2-4(72x-9)/(9x+1)]=4........
解方程:(1+x)[2(-36x)^2/(9x+1)^2-4(72x-9)/(9x+1)]=4.
.......
解方程:(1+x)[2(-36x)^2/(9x+1)^2-4(72x-9)/(9x+1)]=4........
(1+x)[2(-36x)²/(9x+1)²-4(72x-9)/(9x+1)]=4
(1+x)[2(-36x)²/(9x+1)²-4(72x-9)(9x+1)/(9x+1)²]=4
(1+x)×[2×(-36x)²-4×(72x-9)(9x+1)]/(9x+1)²=4
(1+x)×[2×(-36x)²-4×(72x-9)(9x+1)]=4×(9x+1)²
(1+x)×[2×1298x²﹣4×(648x²﹣9x﹣9﹚=4×(81x²﹢18x﹢1﹚
(1+x)×﹙2592x²﹣2592x²﹢36x﹢36﹚=4×(81x²﹢18x﹢1﹚
(1+x)×﹙36x﹢36﹚=4×(81x²﹢18x﹢1﹚
4×(1+x)×﹙9x﹢9﹚=4×(81x²﹢18x﹢1﹚
(1+x)×﹙9x﹢9﹚=81x²﹢18x﹢1
9x﹢9x²﹢9﹢9x=81x²﹢18x﹢1
9x²﹢18x﹢9=81x²﹢18x﹢1
81x²﹢18x﹢1﹣9x²﹣18x﹣9=0
72x²﹣8=0
72x²=8
x²=72÷8
x²=9
x=√9
x=±3
我晕!!!!!!!!!!
解方程:(x+2)(x+2)-x*x=36
解方程x/(x-2)=2x/(x-3)+(1-x)/(x-5x+6)
解方程(x/x(x+2))+(x/(x+2)(x+4))+.+x/(x+8)(x+10)=1
解方程:x(x-1)+x(2+x)=2x(x-2)
解方程2x/x+2-x/x-2-x+11/4-x方=1
解方程:(x-1)/(x²-2x)+x(2-x)=1/x
解方程:2x(x-2)-6x(x-1)=4x(1-x)+16
x/(x-2)+(x+1)/(x-6)=2x/(x-3) 解分式方程
解方程(x-3/x)-(3-x/x+1)=5x-15/2x+2
解方程X(X+1)-X(X-3)=2(X+1)(X-1)+20
解方程((13x-x^2)/(x+1))(x+(13-x)/(x+1))=42
解方程 3x/x×x-1+x×x-1/3x=5/2
解方程[(19x-x^2)/(x+1)][x+(19-x)/(x+1)]=84.
解方程:(19x-x^2)/(x+1)*(x+(19-x)/(x+1))=84
解方程x(x-1)(x-2)(x-3)(x-4)=24x=?
解方程 x(2x-4)+3x(x-1)=5x(x-3)+8
解方程(x²-x+4)x-(x-1)(x²+2)=x+7
解方程 X(X+1)x(X+2)x(X+3)=3024